The promising oncostatic effects of melatonin against ovarian cancer: Melatonin and ovarian cancer (World Journal of Current Medical and Pharmaceutical Research, 2021)
Melatonin is a pineal hormone, secreted at the subjective night. It is involved in the regulation of many physiological functions, including the sleep-wake cycle, gonadal activity, free radical scavenging, immunomodulation, neuro-protection, and cancer progression. Melatonin acts through cell surface receptors (MT1 and MT2) as well as nuclear receptors. Circadian dysfunction can alter the secretion of melatonin. Inappropriate melatonin level promotes the initiation of many pathologies including cancer. Ovarian cancer is a common form of gynecological disease. Several studies indicate the profound link between impaired melatonin secretion and the progression of ovarian cancer. Melatonin exerts oncostatic effects in multiple ways; it acts as a potent antioxidant, induces apoptosis, and regulates metabolism, and chronic inflammatory response in ovarian cancer cells. Moreover, melatonin improves the efficacy of the current treatment regimen of ovarian cancer and can be used as an adjuvant.